The role of non-coding sequences in melanoma carcinogenesis - Kwinta, Łukasz (Contemporary Oncology/Współczesna Onkologia, 2008)
The incidence of skin melanoma is increasing, with the number of new cases rising at one of the highest rates. That is why melanoma is becoming one of the key points of interest among oncologists. Findings concerning non-coding sequences (NCS) of nucleic acids are of great importance for our understanding of its pathogenesis. NCS do not code sequences of proteins but play a key role in the regulation of virtually all steps of genetic material expression. The main classes of NCS are: gene promoters, enhancers (responsible for regulation of transcription level), sequences localized in introns (playing a role in splicing), 5’UTRs and 3’UTRs (untranslated regions of mRNA localized on both sides of the coding sequence). This review is focused on the current state of knowledge in the role of NCS in melanoma carcinogenesis.